A Greedy Algorithm on Constructing the Minimum Connected Dominating Set in Wireless Network. (14th July 2016) - Fu, Deqian; Han, Lihua; Yang, Zifen; Jhang, Seong Tae
In the past 20 years, the connected dominating set (CDS) as a virtual backbone network has been widely used in the wireless networks. Many researchers have been devoted to designing approximate algorithms for CDS problem since constructing the minimum CDS (MCDS) is NP-hard problem. Different from the most existing algorithms with two phases, we employ greedy strategy to design a centralized algorithm GR_CDS in only one phase to get MCDS, with the time complexity ofO ( ( Δ 2 + log ⁡ n ) n ) . Afterwards, another algorithm P_CDS is designed for pruning redundant nodes in the obtained MCDS with the time complexity ofO ( n 2 ) .